2007
DOI: 10.1016/j.brat.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

High self-reported rates of neglect and emotional abuse, by persons with binge eating disorder and night eating syndrome

Abstract: This study compared rates of self-reported childhood maltreatment in three groups diagnosed using semi-structured interviews: binge eating disorder (BED; n = 176), night eating syndrome (NES, n = 57), and overweight/obese comparison (OC, n = 38). We used the Childhood Trauma Questionnaire (CTQ) to assess childhood maltreatment and the Beck Depression Inventory-II to assess depression levels. Reports of maltreatment were common in patients with BED (82%), NES (79%), and OC (71%). The BED group reported signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 42 publications
(37 reference statements)
5
64
2
7
Order By: Relevance
“…When compared with a BED group, BMI was not found to differ between NES and BED in either a diabetic sample 33 or a sample recruited by advertisement. 34 Colles et al 36 reported that NES correlated with BMI in a sample of bariatric surgery candidates. In these studies, depressive symptoms and diagnosis have generally been more frequent in the NES group.…”
Section: Studies Of Clinical Correlates Of and Potential Riskmentioning
confidence: 98%
See 2 more Smart Citations
“…When compared with a BED group, BMI was not found to differ between NES and BED in either a diabetic sample 33 or a sample recruited by advertisement. 34 Colles et al 36 reported that NES correlated with BMI in a sample of bariatric surgery candidates. In these studies, depressive symptoms and diagnosis have generally been more frequent in the NES group.…”
Section: Studies Of Clinical Correlates Of and Potential Riskmentioning
confidence: 98%
“…Hence, in this study binge eating but not night eating was associated with psychopathology. Allison et al 34 compared treatment seeking individuals with NES (n 5 57), BED (n 5 176), or obesity (non-ED, n 5 38) on history of childhood maltreatment. Those with NES differed significantly from obesity controls only on one of five comparisons (''emotional abuse''), with 51% of NES patients and 32% of controls reporting this form of maltreatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As reports of abuse in women with BED are high (Allison et al, 2007;, increased categoric recall in women with BED may on the other hand represent an avoidance reaction of negative intrusive imagery such as past binge attacks or other negative experiences and feelings (Conway & Pleydell-Pearce, 2000;Williams et al, 2007). In AN, for example, level of self reported parental abuse was significantly and positively correlated with overgenerality (Dalgleish et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As specific memories primarily involve sensory-perceptual information, they may produce increases in mood disturbance, which both women with AN and BED may try to avoid. As traumatic experiences are increased in BED women compared to HC (Allison et al, 2007;), we did not do any mediation analyses (Miller & Chapman, 2001) with traumatic history. Therefore, to better understand the role of traumatic history in the recall of AM, future studies should compare BED women with and BED women without traumatic history with regard to AM recall.…”
Section: Discussionmentioning
confidence: 99%